Examining patronage intentions of customers: a case of green hotels - Shrivastava, Priyanka; Gautam, Vikas (Frontiers in Sustainable Tourism, 2024)
This research paper explores the increasing significance of sustainability within the hospitality industry, focusing on how customers' patronage intentions are influenced by green hotels. Amid rising global awareness of environmental issues, the study investigates the effect of hotels' green initiatives on customer behavior and decision-making. The analysis employs theories such as the Theory of Reasoned Action (TRA) and the Theory of Planned Behavior (TPB) to examine the roles of environmental awareness, personal norms, and perceived behavioral control in shaping consumer choices at green hotels.The methodology involves a detailed survey of 418 travelers in India, evaluating their attitudes towards green hotels and how these attitudes impact their sustainable consumption behaviors.Findings from 397 valid responses indicate that well-informed consumers are more likely to support and prefer hotels committed to sustainability, positively affecting their purchasing decisions and loyalty.The research enhances understanding of consumer behavior in sustainable tourism, providing important insights for hotel managers and policymakers. It underscores the importance of incorporating green practices into business strategies to appeal to environmentally conscious customers and emphasizes the need for continuous engagement and transparency in promoting environmental values, which are crucial for boosting customer satisfaction and loyalty in the hospitality industry.